Curriculum guidelines for entrepreneurial skills development : a Pan-Commonwealth technical meeting - Curriculum Guidelines for Entrepreneurial Skills Development : A Pan-Commonwealth Technical Meeting (1989 : Genting Highlands); Malaysia. Kementerian Pendidikan (Kuala Lumpur : Ministry of Education, 1989)
32